Design and Analysis of Squeezing Ground Hydropower Tunnel in the Himalaya through a Case Study - S. Karki; B. Karki; B. Chhushyabaga; S.S. Khadka (International Association of Lowland Technology, 2020)
Nepal is a country with varying topography and steep fast flowing rivers, high head hydropower projects are preferred in the region. Currently, numerous hydropower tunnels are being constructed and many more have been proposed. The varying geology along with weak rock mass has created several stability problems like squeezing and support failures. Through a case study in the Lesser Himalayan Region, this paper focuses on the assessment and analysis of tunnel sections in squeezing ground through analytical and numerical modelling. The most commonly adopted Rock Mass Classification approach for estimation of tunnel support seems inadequate to address the problem associated with tunneling in the Himalayas. Therefore, the knowledge of rock mass strength and deformation behavior is required for the optimal design of tunnel support in such geological conditions. Finite element analysis is carried out for face stability of tunnel in very poor rock mass by improving the rock mass to predict the real behavior of squeezing ground. The results of the analysis show that along with the use of empirical and analytical approach, numerical analysis should be used from the preliminary stages of design and care should be taken while modelling very poor rock mass where the stability of rock ahead of tunnel face is essential.